Effects of roasting on proanthocyanidin contents of Turkish Tombul hazelnut and its skin. (May 2016) - Lainas, Katherine; Alasalvar, Cesarettin; Bolling, Bradley W.
Highlights: Hazelnut bound proanthocyanidins were previously uncharacterised. Alkaline hydrolysis of hazelnut releases unextractable proanthocyanidins. Hazelnut skin is rich in proanthocyanidin oligomers. The proanthocyanidin profile of hazelnut varies significantly by product type. The level of extractable and bound proanthocyanidin in natural hazelnut is similar. Abstract: The effects of roasting on extractable and bound proanthocyanidins of Turkish Tombul hazelnut and its skin were studied. Natural (raw) and roasted hazelnuts as well as roasted hazelnut skin were extracted, hydrolysed, and analysed by normal-phase high performance liquid chromatography. Natural hazelnut extractable proanthocyanidins were 81% oligomers (4–9mers) and polymers (≥10mers). However, roasted hazelnut extractable proanthocyanidins were only monomers to trimers. This decrease was apparently due to skin loss during roasting. Additional proanthocyanidins of roasted hazelnut residue were recovered by alkaline hydrolysis. In contrast, natural hazelnut had proportionally less bound proanthocyanidins, mainly as dimers. Roasted hazelnut skin proanthocyanidins were 21% bound with mainly dimers, trimers, and tetramers recovered after alkaline hydrolysis. These data suggest that prior studies may have underestimated hazelnut proanthocyanidin content because a significant quantity of bound proanthocyanidins is not recoverable by conventional organic solvent extraction.